The Influence of Organizational Culture And Job Satisfaction On Employee Performance With Job Stressas A Mediating Variable In The Employment Bpjsbranch Office In Medan Raya - Nasution, Rizky Ira Silvia; B, Mesra (Best Journal of Administration and Management, 2024)
This study aims to look at the Effect of Organizational Culture and Job Satisfaction on Employee Performance with Job Stress as a Mediating Variable at BPJS Employment Branch Office Se-Medan Raya. This type of research uses quantitative methods, this research was conducted at the BPJS Ketenagakerjaan Branch Office in Greater Medan, the population used was 80 employees consisting of 20 personnel from Medan Kota, 20 personnel from North Medan, 20 personnel from Tanjung Morawa and 20 personnel from Binjai. The sample used is all the population of 80 employees with saturated samples being the sample technique. The data source used is primary data source and data collection by distributing questionnaires. This research model uses phat analysis and the measuring tool is the smart PLS version 3.3.3 application. The results of this study are as follows: Organizational culture has a positive and significant effect on employee performance with an original sample value of 0.285 and p values of 0.045. Organizational culture has a positive and significant effect on Job Stress with an original sample value of 0.628 and P values of 0.000. Job satisfaction has a positive and significant effect on employee performance with an original sample value of 0.492 and p values of 0.000. Job satisfaction has a positive and significant effect on Job Stress with an original sample value of 0.281 and p values of 0.007. Job Stress has a positive and insignificant effect on employee performance with an original sample value of 0.191 and p values of 0.149. Organizational culture has a positive and insignificant effect on employee performance through work stress indirectly with the original sample result of 0.120 and p values 0.165. Job satisfaction has a positive and insignificant effect on employee performance through job stress with an original sample value of 0.054 and p values of 0.234.